Determination of complex permeability of materials in the context of loss reduction in submarine cables - Tudorache, Adriana; Mylvaganam, Saba; Thiriet, Jean Marc; Timmerberg, Josef (Proceedings of the International Conference on European Association for Education in Electrical and Information Engineering, 2023)
Many thousand subsea power cables are already in use between Norway, Germany, UK in Europe, and other countries in the world. Losses in these cables have not only economic but also environmental consequences. These losses at power frequencies can be estimated using field theoretic methods. For determining the losses within the steel wire armouring of subsea power cables, knowledge of the magnetic properties is essential to include losses caused by eddy currents, cyclic magnetization, and hysteresis. One possibility of taking magnetic material properties into account is using complex relative permeability. There are different methods of measuring the complex permeability of materials. The measurement procedures depend on the cross-sectional geometry of the materials to be tested, e.g., flat sheet, square rod etc.In this paper, the material under test (MUT) for permeability measurements is in the form of cylinders with concentric primary (for excitation) and secondary (for sensing) windings for electromagnetic excitation and measurements. Using the measured voltages and currents in these windings, the hysteresis loop is generated. From this the complex permeability of the material is then estimated. The paper addresses interdisciplinary thinking in the design, testing and commissioning of sub-sea power cables. Through the usage of COMSOL Multiphysics, modern IT-tools are used to test and validate the models developed and algorithms used in the determination of the complex permeability. Using COMSOL Multiphysics, leads to some interesting gamification of the subject content in the curricula, as different groups can be assigned different tasks to check and cross-check the results. This topic thus opens different channels for exploration involving industry and academia.